The Profitability of Ukrainian Enterprises: Current Status, Dynamics, Ways of Increasing - Melnyk Alona О.; Shtefan Liudmila І. (Bìznes Inform, 2018)
The article considers the essence of profit of enterprises and examines the main tendencies of profitableness of the status of national enterprises over the last five years. The main reasons of decrease of profitableness of national enterprises are determined. The structure of net profit of Ukrainian enterprises is considered by types of economic activity. The ratio of profitable and unprofitable enterprises in Ukraine is analyzed, the dynamics of profitable enterprises is identified. The analysis of the profitability level of national enterprises on the results of operations is carried out. It is proposed to apply the scale of profitableness in order to increase the level of profitability at national enterprises.